Effects of Morinda citrifolia Leaf Extract on Glucose Absorption through Intestinal Epithelial Membrane in Wistar Rat Models - Shalim, Rikho Melga; Syamsunarno, Mas Rizky A. A.; Shahib, Muhammad Nurhalim (Althea Medical Journal, 2017)
Background: Noni fruit (Morinda citrifolia) has been used as herbal medicine by Indonesian people. However, the effect of noni leaves as an antihyperglycemic agent is still unknown. This study was conducted to find out the effect of Morinda citrifolia leaves on glucose absorption through intestinal epithelial membrane in wistar rat models.Methods: The study was conducted in November 2015 at the Biochemistry and Molecular Biology Laboratory Faculty of Medicine, Universitas Padjadjaran. We used in situ perfusion and rats were divided into 2 groups. The first group used glucose solution as a control. The second group used glucose with extracts. Specimens were taken before and after perfusion to check the amount of glucose with spectrophotometer. Statistical analysis using t-test was conducted to compare the total absorbed concentration of glucose from each group. Results: From calculation we found the kinetic value (Km) of glucose absorption without extract (Km=17.24) and with extract (Km=16.67). Statistical test showed there was no significant in results (p>0.05).Conclusions: There is no effect of Morinda citrifolia leaf extract on glucose absorption. However, kinetics of glucose absorption suggested a non-competitive inhibition by Morinda citrifolia leaf extract.Â